PEMBELAJARAN MELALUI OBSERVASI UNTUK MENGEMBANGKAN KETERAMPILAN FISIK DAN TANGGAPAN PSIKOLOGIS DALAM OLAHRAGA - Suharjana Suharjana (LPMPP Universitas Negeri Yogyakarta, 2007)
Observational learning is one of the activating methods tochange ideas, emotions, and actions in various sports. Lately,observational learning for the sake of the appeal of a psychologicalmethod in sports has been ignored by teachers of physical educationand coaches. This article is hopefully to help convince researchersand practitioners not to forget observational learning as an effectivemethod for the development of skills and psychological responses insports. For that purpose, the article will discuss respectively casestudies in sport activities, the theoretical approach to observationallearning, motor skills and psychological responses, developmentalissues, and possible interventions for Makaila, Harrison, and Feliciaas individuals who have problems in sports.Modeling interventions are highly effective as methods ofdeveloping skills and psychological responses in physical activities.Theories, researches, and applications have given teachers ofphysical education and coaches convincing reasons for the reuse ofobservational learning as a learning method that could developphysical skills and psychological responses in sports. Modelstudying, self-observation techniques, peer models, and imitativemodels are part of the intervention types available that could be usedon children and adults in sport practices, sport competitions, andrehabilitative situations.